Hospital Ambulance Standardization in Jakarta: Narrative Review - Suranta, Roy Michael; Gani, Ascobat (Journal of Indonesian Health Policy and Administration, 2023)
Ambulance is one of the hospital infrastructures that must meet service standards, security, and occupational safety and health in hospital operations. Therefore, it is the obligation of every hospital to ensure the standard of ambulance service. In the DKI Jakarta area, every ambulance, including hospital ambulances, must meet the standards in accordance with regulations and have an ambulance operating license. Based on data until the end of 2021, there were 82 (34.9%) hospital ambulances in Jakarta that carried out the recommendation process for an ambulance operation license from a total of 235 hospital ambulances, meaning that most hospital ambulances in Jakarta did not meet service standards. DKI Jakarta Governor Regulation number 120 of 2016 concerning Ambulance Services and Hearse is a reference for hospitals in Jakarta in order to meet ambulance service standards. In conclusion, there are 3 (three) standards that must be met in standardizing hospital ambulance services in Jakarta, namely standardization of vehicle units, standardization of equipment and standardization of human resources.